Relationship between Education, Parity Status and Mother's Knowledge of Booster Immunization with Complete Basic Immunization of Children in the Work Area of the Tanjungsiang Health Center Subang Regency in 2023 - Malinda, Devi; Rismayanti, Tetin (CV. Inara, 2024)
Complete basic immunization plays a role in suppressing the spread of disease so that it is beneficial for immunity. In reducing the incidence of disease, complete basic immunization is needed to reduce disease in society as a whole.Purpose of Writing: for Education Relations, Parity Status and Mother's Knowledge About Booster Immunization With Children's Complete Basic Immunization. Research Methods: the sample was taken by all mothers who had toddlers aged 24-59 months. data collection using secondary and primary data. primary and secondary data collection. research design cross sectional quantitative approach. Research Results : In the results of the study, the majority of mothers with high school education (SMA) were 32 people (55.2%), parity status of primipara mothers were 29 people (50.0%), good knowledge of 26 people (44.8%) . There is a relationship between parity and knowledge of complete basic immunization with an asym sig 2 tailed value of 0.05 for parity status and 0.000 for knowledge. There was no relationship between education and complete basic immunization, which resulted in an asym sig 2 tailed value of 0.887. Conclusions and Suggestions: In providing education to mothers having babies 0-59 months, midwives can collaborate with other health teams, in providing health education about immunization.